miR-24-3p secreted as extracellular vesicle cargo by cardiomyocytes inhibits fibrosis in human cardiac microtissues - Senesi, Giorgia; Lodrini, Alessandra M; Mohammed, Shafeeq; Mosole, Simone; Hjortnaes, Jesper; Veltrop, Rogier J A; Kubat, Bela; Ceresa, Davide; Bolis, Sara; Raimondi, Andrea; Torre, Tiziano; Malatesta, Paolo; et al. (Cardiovascular research, 2025)
Cardiac fibrosis in response to injury leads to myocardial stiffness and heart failure. At the cellular level, fibrosis is triggered by the conversion of cardiac fibroblasts (CF) into extracellular matrix-producing myofibroblasts. miR-24-3p regulates this process in animal models. Here, we investigated whether miR-24-3p plays similar roles in human models. Gain- and loss-of-function experiments were performed using human induced pluripotent stem cell-derived cardiomyocytes (hCM) and primary hCF under normoxic or ischaemia-simulating conditions. hCM-derived extracellular vesicles (EVs) were added to hCF. Similar experiments were performed using three-dimensional human cardiac microtissues and ex vivo cultured human cardiac slices. hCF transfection with miR-24-3p mimic prevented TGFβ1-mediated induction of FURIN, CCND1, and SMAD4-miR-24-3p target genes participating in TGFβ1-dependent fibrogenesis-regulating hCF-to-myofibroblast conversion. hCM secreted miR-24-3p as EV cargo. hCM-derived EVs modulated hCF activation. Ischaemia-simulating conditions induced miR-24-3p depletion in hCM-EVs and microtissues. Similarly, hypoxia down-regulated miR-24-3p in cardiac slices. Analyses of clinical samples revealed decreased miR-24-3p levels in circulating EVs in patients with acute myocardial infarction (AMI), compared with healthy subjects. Post-mortem RNAScope analysis showed miR-24-3p down-regulation in myocardium from patients with AMI, compared with patients who died from non-cardiac diseases. Berberine, a plant-derived agent with miR-24-3p-stimulatory activity, increased miR-24-3p contents in hCM-EVs, down-regulated FURIN, CCND1, and SMAD4, and inhibited fibrosis in cardiac microtissues. These findings suggest that hCM may control hCF activation through miR-24-3p secreted as EV cargo. Ischaemia impairs this mechanism, favouring fibrosis.